Politik Pembangunan Wisata Halal di Kota Sabang - Ulfa, Mau Lida; Kusmanto, Heri; Warjio, Warjio (Jurnal Administrasi Publik : Public Administration Journal, 2019)
This study is about political development of halal tourism in Sabang city. The focuses of this study are to analyze the actors of political development of halal tourism in Sabang city, the strategy, also the chances and challenges. The method used is a qualitative method. The findings of this study, among others, there are three important points. First, the actors of political development who invlolved are categorized at the national, Individual (national), Local (Aceh Province), Individual (Aceh Province), Local (Sabang), Individual (Sabang), and Private (Sabang) levels. Second, the actors who involved use a political development strategy with a mixed approach. Third, the actors see the magnitude of opportunities in building halal tourism in Sabang city and also the challenges that must be overcome immediately to manifest this.